Electronic structure and x-ray magnetic circular dichroism of Mn-doped TiO2 - Bekenov, L.V.; Antonov, V.N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The electronic structure of (Ti,Mn)O2 diluted magnetic semiconductors was investigated theoretically from first principles using the fully relativistic Dirac linear muffin-tin orbital band structure method. The electronic structure was obtained with the local spin-density approximation taking into account strong Coulomb correlations in the frame of the LSDA + U approximation. The x-ray absorption spectra and x-ray magnetic circular dichroism spectra at the Mn and Ti L2,3 and O K edges were investigated theoretically from first principles. The origin of the XMCD spectra in these compounds was examined. The calculated results are compared with available experimental data.